2004
DOI: 10.1080/003434042000211051
|View full text |Cite
|
Sign up to set email alerts
|

A Typology and Assessment of Multi-sector Regional Economic Impact Models

Abstract: Loveridge S. (2004) A typology and assessment of multi-sector regional economic impact models, Reg. Studies38, 305-317. This paper provides a summary and critical review of the types of multi-sector models with inter-sectoral linkages commonly used to predict the total impact of an event (plant opening, closing or policy change) on the regional economy. The following model types are included: economic base; input-output; social accounting matrix; integrated econometric/input-output; and computable general equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 0 publications
0
58
0
12
Order By: Relevance
“…The high level of resulting disaggregation available in some off-the-shelf modeling packages can create a false sense of precision, with the model reflecting inter-industrial linkages for sectors that may not exist or that exist at a different level or in different form than predicted by national industrial composition data (Loveridge, 2004). Such models are thus better at predicting impacts in hypothetical communities that have the characteristics reflected in the model rather than predicting impacts in actual communities, unless considerable effort is made to calibrate the model to local conditions.…”
Section: Measuring the Local Economic Impacts Of Wind Power Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The high level of resulting disaggregation available in some off-the-shelf modeling packages can create a false sense of precision, with the model reflecting inter-industrial linkages for sectors that may not exist or that exist at a different level or in different form than predicted by national industrial composition data (Loveridge, 2004). Such models are thus better at predicting impacts in hypothetical communities that have the characteristics reflected in the model rather than predicting impacts in actual communities, unless considerable effort is made to calibrate the model to local conditions.…”
Section: Measuring the Local Economic Impacts Of Wind Power Developmentmentioning
confidence: 99%
“…Additionally, project-level case studies might further be questioned because they are often based on self-reported direct employment and income, which may differ from the actual direct employment and income resulting from project operations, particularly when there is an incentive to boost the favorable impression of a project (e.g., Loveridge, 2004). Moreover, by focusing on direct impacts (and often ignoring indirect and induced effects), case studies of actual projects may understate the economic development impacts of wind development.…”
Section: Measuring the Local Economic Impacts Of Wind Power Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A second mechanism, drawing on "staples and vent-for-surplus models" (Findlay and Lundahl, 1994), operates through the backward and forward inter-sectoral linkages generated by the economic-base activities when there are idle resources in the region. Multi-sector and multiregional growth models have been based on these two mechanisms of economic base led models (Loveridge, 2004;Nijkamp, Rietveld and Snickars, 1987).…”
Section: IIImentioning
confidence: 99%
“…Input-output (I/O) modeling and related methods such as social accounting matrix or integrated econometric and I/O modeling are well-established, multi-sector approaches to analyze exogenous or policy-induced economic effects across industries on a national and regional level [15,16]. As its main strengths, I/O modeling builds on an integrated and consistent methodological framework that breaks down the estimated impacts into finely disaggregated industry sectors and then comprehensively measures direct and induced impacts on output or employment .…”
Section: Introductionmentioning
confidence: 99%